2017
DOI: 10.1093/glycob/cwx069
|View full text |Cite
|
Sign up to set email alerts
|

Pectobacterium atrosepticum exopolysaccharides: identification, molecular structure, formation under stress and in planta conditions

Abstract: In the present study, we identified exopolysaccharides of the harmful phytopathogenic bacterium Pectobacterium atrosepticum SCRI1043 and characterized the molecular structure of these polymers. The synthesis of the target polysaccharides was shown to be induced under starvation conditions. Moreover, intensive accumulation of exopolysaccharides occurred during the colonization by bacteria of the xylem vessels of infected plants, where microorganisms formed specific 3D "multicellular" structures-bacterial emboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 68 publications
0
15
0
1
Order By: Relevance
“…Despite the diversity of species and strains comprising SRP, very limited information is available on both the composition of polysaccharides of Pectobacterium and Dickeya, and the details of phage interaction with the polysaccharides. Only eight structures of polysaccharides of P. atrosepticum [36,46,47], P. wasabiae [48], P. carotovorum (then Erwinia carotovora subsp. carotovora) [49], P. brasilense [45] and D. solani [44,50] have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the diversity of species and strains comprising SRP, very limited information is available on both the composition of polysaccharides of Pectobacterium and Dickeya, and the details of phage interaction with the polysaccharides. Only eight structures of polysaccharides of P. atrosepticum [36,46,47], P. wasabiae [48], P. carotovorum (then Erwinia carotovora subsp. carotovora) [49], P. brasilense [45] and D. solani [44,50] have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, it was Pba enzymes that cleaved Gal side chains of RG-I since three Pba β-galactosidase/endo-β-1,4-galactanase genes were upregulated in planta ( Table S3 ) and none of plant β-galactosidase genes were upregulated during the infection, while most of them were downregulated ( Table S2 ). Such kinds of low-Gal-substituted, 50–400 kDa RG-I fragments were previously shown to prime the assemblage of bacterial emboli, forming an initial extracellular matrix that was further substituted by Pba exopolysaccharides [ 10 , 34 ]. It should be noted that the bacterial polysaccharides were unlikely to contribute to the obtained data: first, we have previously shown that the portion of bacterial polysaccharides is negligible in the whole polysaccharide pool of the infected plant [ 10 ], and second, exopolysaccharides of Pba have the specific content and proportion of monosaccharides [ 34 ], and thus, their contribution to the whole carbohydrate pool would be evident if this was the case.…”
Section: Discussionmentioning
confidence: 99%
“…We were somewhat surprised by the finding that survival of A. baumannii and P. atrosepticum was much lower than the other strains tested, as both organisms are considered to have a high ability to persist in their environments. Interestingly, both organisms have previously been observed to secrete carbon-containing metabolites into their environments at the entry to stationary phase [Gorshkov et al, 2017;Zeidler and Müller, 2020]. These activities have been proposed to contribute to strategies for tolerating desiccation [Zeidler and Müller, 2019] (A. baumannii does have a remarkable ability to survive desiccation [Harding et al, 2018]) or for preparing for plant infection [Gorshkov et al, 2017].…”
Section: Pseudomonasmentioning
confidence: 99%
“…Interestingly, both organisms have previously been observed to secrete carbon-containing metabolites into their environments at the entry to stationary phase [Gorshkov et al, 2017;Zeidler and Müller, 2020]. These activities have been proposed to contribute to strategies for tolerating desiccation [Zeidler and Müller, 2019] (A. baumannii does have a remarkable ability to survive desiccation [Harding et al, 2018]) or for preparing for plant infection [Gorshkov et al, 2017]. However, under the particular conditions of this experiment, where the stationary phase culture medium was removed and a long-term carbon starvation followed, jettisoning carbon resources at the beginning of the starvation may have been maladaptive.…”
Section: Pseudomonasmentioning
confidence: 99%